Crossing Borders and Building Bridges: A Video Ethnography of Special Education in Nuevo Progresso, Mexico - Lowdermilk, John; Pecina, Julie; Fielding, Cheryl; Beccera, Lisa (Journal of the American Academy of Special Education Professionals, 2016)
This paper presents an overview of a video ethnographic study of a special education school on the Texas/Mexico Border. The public school is located in Nuevo Progreso, which is a town in the Río Bravo Municipality in the state of Tamaulipas in Mexico. The town is located on the United States-Mexico border. The Progreso-Nuevo Progreso International Bridge connects the town with Progreso Lakes, Texas. The 2010 census showed a population of 10,178 inhabitants. Both the school and town have very little resources making the creation of the special education school a very special event. For a public school to start a program requires many people (e.g., parents, teachers, school officials, students, and other stakeholders) bringing many resources to the table. One group was able to bring together the people and the resources.